Implementasi Augmented Reality Sebagai Media Pembelajaran Technical Support Berbasis Android - Pribadi, Antoni; M.Kom, Fitri; Nasari, Fina (Universitas Asahan, 2024)
The current development of technology is in society 5.0 which states the concept that technology will coexist with humans to improve the quality of life in a sustainable manner. One of the technologies that is developing today is augmented reality. Augmented reality is a potential technology developed in various aspects of life by combining objects in the real world in real time that is interesting. Augmented reality technology can be implemented in various fields, one of which is in the field of education, because it can be used as a learning medium. The field of education always adjusts technological developments to improve the quality of learning both in quality and quantity of the lessons themselves. This research aims to develop an application Implementation of Augmented reality as an Android-Based Technical Support Learning Media using 3D technology in the teaching and learning process can help students to remember the names and functions of computer components. The method used in completing this final project is the Luther Sutopo method. Application Development using Unity Software, blender, and vuforia SDK. The results of this study succeeded in making the application of Augmented reality Implementation as an Android-Based Technical Support Learning Media.